Monitoring structure and coordination chemistry of Co4O4-based oxygen evolution catalysts by nitrogen-14/-15 and cobalt-59 NMR spectroscopy - Uhlig, Felix; Stammler, Michael B.; Meurer, Florian; Shenderovich, Ilya G.; Blahut, Jan; Wisser, Florian M. (Dalton Transactions, 2024)
The structural features of cobalt-based oxygen evolution catalysts are elucidated by combining high-field MAS NMR spectroscopy and DFT calculations. The superior photocatalytic activity of the heterogeneous system over its homogeneous counterpart is rationalised by the structural features. The higher activity is caused by a more favourable electron-withdrawing character of the framework.
CRIS-Team Scopus Importer:2024-05-17